Co‐morbidities and mortality associated with transfusion‐dependent beta‐thalassaemia in patients in England: a 10‐year retrospective cohort analysis. (23rd October 2020) - Jobanputra, Minesh; Paramore, Clark; Laird, Sandra G.; McGahan, Michael; Telfer, Paul
Summary: A retrospective cohort analysis to explore 10‐year mortality and prevalence of transfusion‐dependent β‐thalassaemia (TDT)‐associated co‐morbidities in patients with TDT was undertaken using Hospital Episode Statistics (HES) data from the National Health Service (NHS) in England. A 10‐year forward‐looking cohort analysis for the period 2009–2018 was completed using HES admitted patient care (APC), outpatient data, and linked HES/Office of National Statistics mortality data for patients with β‐thalassaemia (ICD‐10 diagnosis code D56.1). TDT‐associated co‐morbidity rates were high in the 612 patients with TDT, with 76% having at least one co‐morbidity, 54% suffering from two of more, and 37% three or more. The three most common TDT‐associated co‐morbidities, occurring in more than one third of patients were: endocrine disorders (excluding diabetes) 40%, osteoporosis 40%, and diabetes 34%. Cardiac disease was observed in 18% of patients overall, with atrial fibrillation and heart failure being the most common with a prevalence of 11% and 9%, respectively. The crude 10‐year mortality rate in the TDT cohort was 6·2% (38/612), significantly greater than the 1·2% age/sex‐adjusted mortality rate of the general population ( P < 0·001). These data support the notion that the unmet need in TDT remains significant, with high rates of co‐morbidity and mortality.